CATALOGUE OF MAIN CHARACTERISTICS OF PULSATIONS OF 173 SEMI-REGULAR STARS - Chinarova, L. L; Andronov, I. L. (Одеські астрономічні публікації, 2017)
The characteristics of brightness variations of 173 semi-regular stars are tabulated: the moments and brightness of the extrema; the effective periods, amplitudes and significance obtained by using different methods: a) the periodogram analysis (harmonic least squares t) with prewhitening to determine characteristics and significance of waves with 3 periods; b) the wavelet analysis to determine characteristics of statistically significant waves; ) the "running parabola" scalegram analysis to determine the optimal filter half - width for smoothing. The characteristics may be used for more precise classification of semi-regular variables. Characteristics of the 6509 extrema of 147 stars are listed. The electronic version is available via http://ila.webjump.om. The observations for the analysis have been taken from the AFOEV and VSOLJ databases (with a duration up to 94 years) for the stars: AQ, EH, EK, RS, RU, RV, ST, TV, TY, TZ, UX, VX And; GY, PX, S, V, V844 Aql; V, Z Aqr; T Ari; AG, RS, S, UU, Z Aur; RV, RW, RX, RZ, U, V, WY Boo; T Cae; RR, RS, RY, S, ST, U Cam; RT Cap; PZ, SV, UX, V393, V465, WZ Cas; T, Y Cen; AR, RU, RW, RX, SS, TY, W Cep; T Cet; RS, RT, T, X Cnc; RR, RS, TT CrB; V, Y Cvn; AA, AF, AI, AV, AW, BC, RS, RU, RV, RW, RZ, TT, V460, W Cyg; EU, U Del; RS, RY, S, TX, UX, WZ Dra; SY, Z Eri; IS, NQ, RS, SW, TU, TV, Y Gem; DE, MZ, RR, ST, SX, UU, X Her; FF, RT, U, V, W, Y Hya; RS Lac; RY, SX Leo; RX, S Lep; U, W LMi; Y, EG, R, SZ Lyr; RV, SW, X Mon; V759 Oph; BQ, FX, GT, RT, W Ori; AF, AK, SV, TX Peg; AD, BU, DY, FZ, RS, RU, S, SU, SY, T, UZ, W, XX Per; R Pic; RT, RW, Z Psc; BM Sco; S Sct; FG Ser; X Sge; AB, TT, W, Y Tau; W Tri; RX, RY, RZ, ST,SV, V, Y, Z UMa; R, V UMi; RT, SS, SW Vir; RU Vul.